2008
DOI: 10.1097/mpg.0b013e318174e808
|View full text |Cite
|
Sign up to set email alerts
|

Germline APC Mutations Are Not Commonly Seen in Children With Sporadic Hepatoblastoma

Abstract: Hepatoblastoma is the most common primary liver tumor in childhood and occurs more commonly in families with familial adenomatous polyposis. Germline mutations of the gene responsible for familial adenomatous polyposis--adenomatous polyposis coli (APC)--are described in patients with hepatoblastoma even without a family history. We investigated children presenting with apparently sporadic hepatoblastoma between 1991 and 2004. Blood samples were available from 29 children (18 boys) whose conditions were diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Although several studies did not find evidence of pathogenic germline APC mutations in patients presenting with apparent sporadic HB, earlier studies indicated approximately 10% of children with HB have germline APC mutations in the absence of positive family history for FAP . Interestingly, the studies reporting no evidence of clinically consequential germline APC mutations in sporadic HB acknowledged the presence of silent APC point mutations (4/29 patients, 13%), and abnormal β‐catenin accumulation (15/21 patients, 71%) in their respective sporadic HB populations . It is possible that HB tumors with somatic beta‐catenin mutations will be found only in non‐FAP patients based on the notion that somatic beta‐catenin mutations and germline APC mutations are mutually exclusive in HB.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although several studies did not find evidence of pathogenic germline APC mutations in patients presenting with apparent sporadic HB, earlier studies indicated approximately 10% of children with HB have germline APC mutations in the absence of positive family history for FAP . Interestingly, the studies reporting no evidence of clinically consequential germline APC mutations in sporadic HB acknowledged the presence of silent APC point mutations (4/29 patients, 13%), and abnormal β‐catenin accumulation (15/21 patients, 71%) in their respective sporadic HB populations . It is possible that HB tumors with somatic beta‐catenin mutations will be found only in non‐FAP patients based on the notion that somatic beta‐catenin mutations and germline APC mutations are mutually exclusive in HB.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, accurate family history may not always be available, which could result in a failure to diagnose this genetic condition in a timely manner . Although several studies did not find evidence of pathogenic germline APC mutations in patients presenting with apparent sporadic HB, earlier studies indicated approximately 10% of children with HB have germline APC mutations in the absence of positive family history for FAP . Interestingly, the studies reporting no evidence of clinically consequential germline APC mutations in sporadic HB acknowledged the presence of silent APC point mutations (4/29 patients, 13%), and abnormal β‐catenin accumulation (15/21 patients, 71%) in their respective sporadic HB populations .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that HB is the first manifestation of a de novo APC mutation in a substantial fraction of apparently sporadic HB and recommended routine APC mutation screening in these patients and colorectal surveillance thereafter. In contrast, in a study of Harvey et al [28] no germline APC mutations were found in 29 children with sporadic HB. However, the difference between the APC mutation detection rates in the two studies is not statistically significant [28] and further studies are needed before definite recommendations can be given.…”
Section: Discussionmentioning
confidence: 56%
“…In contrast, in a study of Harvey et al [28] no germline APC mutations were found in 29 children with sporadic HB. However, the difference between the APC mutation detection rates in the two studies is not statistically significant [28] and further studies are needed before definite recommendations can be given. Till then, the following procedure seems appropriate (Fig.…”
Section: Discussionmentioning
confidence: 56%